Analisis Faktor Niat dan Perilaku Pengguna Bank Digital dengan Model TAM & UTAUT2 - Cassandra, Valenora; Bernanda, Devi Yurisca (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
In recent years, the modern era has facilitated many changes with the assistance of internet and technology. The concept of digital transformation has attracted many enthusiasts from various sectors, including the banking industry. In today's digital era, the banking industry is rapidly shifting from traditional platforms to digital, one form of proof of innovation formed due to digital changes is digital bank applications. The goal of this study is to examine the variables influencing the conduct of customer’s intentions and usage behaviour when it comes to digital bank application adoption. The research model used is an integration between Technology Acceptance Model (TAM) and Unified Theory of Acceptance and The Use of Technology2 (UTAUT2) with an additional influencing factor that is Trust. The analysis used is PLS-SEM run by SmartPLS software version 4. The analysis's findings indicate that "Behavioral Intention" is influenced by the variables "Perceived Usefulness," "Price Value," "Trust," and "Habit". While the variables "Perceived Ease of Use", "Social Influence", and "Hedonic Motivation" found to have no effect. The variable "Behavioral Intention" also has a significant impact on "Use Behavior".